MOOC-Based PBL Model to Improve Chemical Literacy Skills In Content, Procedural and Epistemic Knowledge Aspects - Mahbub Alwathoni; Sulistyo Saputro; Sri Yamtinah; Mohammad Masykuri; Suwahono Suwahono (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
This study explores the effectiveness of a MOOC-based Problem-Based Learning (PBL) model in enhancing chemical literacy across three dimensions—content, procedural, and epistemic knowledge—among grade 10 high school students. Employing an explanatory sequential mixed-methods design, the research gathered data through chemical literacy tests, interviews, and observations. The participants comprised 80 students from three districts in Central Java, Indonesia. Quantitative analysis using Rasch modeling revealed a significant improvement in scores, with an average pretest score of 44.82, increasing to 66.50 post-intervention. The effect size of 1.1819 was categorized as